2020
DOI: 10.3389/fphar.2020.00342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Doses of Intrathecal Dexmedetomidine as an Adjuvant Combined With Hyperbaric Ropivacaine in Patients Undergoing Cesarean Section

Abstract: In this study, we aim to investigate the effect of different doses of dexmedetomidine as an adjuvant to hyperbaric ropivacaine in spinal anesthesia for cesarean section. Methods: Seventy-five parturients with American Society of Anesthesiologists (ASA) I or II were anesthetized with intrathecal ropivacaine (12.5 mg) alone (R group) or in combination with dexmedetomidine 3 mg (RD3 group) and 5 mg (RD5 group) to undergo a cesarean section. The anesthetic parameters, postoperative analgesia, stress responses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
4
25
1
Order By: Relevance
“…We observed no side effects from the addition of DEX in this particular patient. These results are consistent with previous research demonstrating that patients did not report DEX-related side effects while receiving it intrathecally as an adjuvant pain therapy [ 18 , 25 ]. Table 1 records the overall side effects experienced by this patient.…”
Section: Discussionsupporting
confidence: 93%
“…We observed no side effects from the addition of DEX in this particular patient. These results are consistent with previous research demonstrating that patients did not report DEX-related side effects while receiving it intrathecally as an adjuvant pain therapy [ 18 , 25 ]. Table 1 records the overall side effects experienced by this patient.…”
Section: Discussionsupporting
confidence: 93%
“…Various intrathecal adjuvants, such as opioids and α -2 agonists (clonidine and dexmedetomidine), can be administered along with ropivacaine [ 24 , 25 ]. In a previous study, intrathecal dexmedetomidine demonstrated prolonged duration of sensory block with minimal side effects [ 24 , 26 ]. It can also be administered intravenously for sedation during spinal anesthesia and has gained popularity due to the prolonged action of the block and patient satisfaction [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, both intrathecal morphine and intrathecal dexmedetomidine provided better analgesia when compared with isobaric bupivacaine (53). Administration of intrathecal dexmedetomidine resulted in improved postoperative analgesia when compared with isobaric bupivacaine or ropivacaine alone [54,55]. Intrathecal dexmedetomidine combined with intrathecal magnesium sulphate or intrathecal morphine improved analgesia which was of longer duration than analgesia produced by magnesium sulphate alone [56,57].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%